The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11845-017-1627-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved mortality outcomes over time for weekend emergency medical admissions

Abstract: No increase in 30-day in-hospital mortality for weekend admissions was found in this study. There has been a substantial reduction in mortality for both weekday and weekend admissions over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…For urgent stroke care, recent studies have shown that temporal variation in mortality is now decreasing17 18 including in London’s centralised ‘hub and spoke’ model19 and in the USA ‘comprehensive stroke centres’ 6. London has eight ‘hub’ units which are designated as hyperacute stroke units (HASUs).…”
Section: Introductionmentioning
confidence: 99%
“…For urgent stroke care, recent studies have shown that temporal variation in mortality is now decreasing17 18 including in London’s centralised ‘hub and spoke’ model19 and in the USA ‘comprehensive stroke centres’ 6. London has eight ‘hub’ units which are designated as hyperacute stroke units (HASUs).…”
Section: Introductionmentioning
confidence: 99%
“…29 Recent research, such as the High-Intensity Specialist-Led Acute Care study, 30,31 have taken this approach to examine the intensity of specialist-led care in emergency medical admissions, focusing particularly on the organisation and delivery of care, and medical staffing. 30,31 In the case of urgent stroke care, recent studies have shown that temporal variation in mortality is now decreasing, 32,33 including in London's hyperacute stroke unit (HASU) model. 34 However, there has been no large-scale, organisational research to understand what creates temporal in consistency, particularly in services that aim to operate consistently over 7 days, such as the London stroke services.…”
Section: Chapter 1 Contextmentioning
confidence: 99%
“…The adverse effect of this reduction in services upon acute care is well established, and a higher mortality has been reported for patients undergoing procedures on the weekend . Furthermore, the admission of a patient to hospital on the weekend has been associated with increased mortality when compared with admission during the week although it is unclear whether these differences in mortality persist after adjustment for weekend differences in patient comorbidities and illness severity …”
Section: Introductionmentioning
confidence: 99%